2015
DOI: 10.1038/ncb3119
|View full text |Cite
|
Sign up to set email alerts
|

Directional Notch trafficking in Sara endosomes during asymmetric cell division in the spinal cord

Abstract: Asymmetric division of neural precursor cells contributes to the generation of a variety of neuronal types. Asymmetric division is mediated by the asymmetric inheritance of fate determinants by the two daughter cells. In vertebrates, asymmetric fate determinants, such as Par3 and Mib, are only now starting to be identified. Here we show that, during mitosis of neural precursors in zebrafish, directional trafficking of Sara endosomes to one of the daughters can function as such a determinant. In asymmetric line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 28 publications
5
101
3
Order By: Relevance
“…The precise mechanisms underlying spindle-cortex crosstalk remains an interesting and unsolved problem. In addition, little is known about the mechanisms that are used to ensure that mitosis and cell division are mechani cally robust 62 and that the various organelles are precisely segregated during division [142][143][144] , or about the mech anisms that are used to bias these processes to achieve the same precision during asymmetric divisions. Finally, very little is known about the evolution of eukary otic cell division, which appears to have its origins in Archaea 2,145 .…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms underlying spindle-cortex crosstalk remains an interesting and unsolved problem. In addition, little is known about the mechanisms that are used to ensure that mitosis and cell division are mechani cally robust 62 and that the various organelles are precisely segregated during division [142][143][144] , or about the mech anisms that are used to bias these processes to achieve the same precision during asymmetric divisions. Finally, very little is known about the evolution of eukary otic cell division, which appears to have its origins in Archaea 2,145 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that in dividing cells of the zebrafish spinal cord SARA segregates asymmetrically, whereas Rab5 distributes symmetrically. In this model, the daughter cells that inherited more SARA-expressing EEs remain as proliferative progenitors through a Notch-dependent pathway, whereas the daughter cells containing fewer SARAexpressing EEs tend to leave the cell cycle and differentiate into neurons (Kressmann et al, 2015).…”
Section: Sara Is Dispensable For the Mitosis And Neurogenesis Of Mammmentioning
confidence: 99%
“…Furthermore, SARA has been shown to be involved in the vesicular trafficking of a variety of proteins, including Delta, Notch, uninflatable, rhodopsin, transferrin and Smad (Coumailleau et al, 2009;Loubéry et al, 2014;Chuang et al, 2007;Hu et al, 2002;Tsukazaki et al, 1998). A recent report revealed that SARA is unequally distributed to the two daughter cells of zebrafish spinal cord neural precursor cells that undergo asymmetric division, and that the expression level of SARA plays a determining role in the cell fate of the daughter cells (Kressmann et al, 2015). In the present study, we investigate the expression level and function of SARA during cortical development of the mouse brain.…”
Section: Introductionmentioning
confidence: 99%
“…The antibody complex specifically binds to the extracellular region of the protein and is uptaken into the cell upon endocytosis of the labeled protein, which allows the tracking of in vivo dynamics of this protein with fluorescent confocal imaging. Previously, the antibody uptake assay was used to study the intracellular trafficking and asymmetric segregation of Delta and/or Notch, in the context of ACD of sensory organ precursor (SOP) cells in Drosophila [1621] and neural precursor cells in zebrafish spinal cord [22]. Here, we describe how the antibody uptake assay is performed to study the in vivo dynamics of DeltaD in radial glia of embryonic zebrafish forebrain, as well as demonstrate its broad applicability to various developmental stages and brain regions.…”
Section: Introductionmentioning
confidence: 99%